Mental Health Implications of COVID-19 in Kenya - Ochillo, Marylyn A; Elsie, Ivy O (Europasian Journal of Medical Sciences, 2020)
Dear Editor, As the COVID-19 pandemic continues to spread rapidly worldwide, it is certainly having an immense effect on the mental wellbeing of people thereby increasing the number of people with elevated levels of stress, depression, or anxiety. Developing country will undoubtedly have serious mental health implications due to the poor or almost non-existent mental health services. In Kenya, mental health is still somewhat neglected mainly because only 0.05% of the Governments’ health budget allocation goes to mental health. The allocated health budget largely focuses on communicable diseases despite the impact of mental health on the Kenyan population. Although there are no accurate data on the prevalence of mental disorders in Kenya, various studies have shown that the prevalence of depression generally varies from 19% in household review studies to 42% among the general population visiting the health facilities. Similar to other African countries, Kenya has a shortage of mental health professionals. Mathari hospital is the country’s only mental referral facility where one nurse handles up to 150 patients. In a country with only approximately 100 psychiatrists serving a population of 45 million, only a third of the psychiatrists work in government health facilities. The rest of the psychiatrists work in private health facilities that are generally more expensive making them inaccessible to the majority of the population due to the unaffordable consultation fees.